Fatigue in developmental coordination disorder: an exploratory study in adults. Issue 1 (2nd January 2018) - Thomas, Marie; Christopher, Gary
ABSTRACT: Background: Fatigue in adult Developmental Coordination Disorder (DCD) is increasingly being acknowledged by clinicians. However, no research to date has explored the nature of fatigue experienced by adults with this disorder. Purpose: This paper aimed to examine fatigue in adult DCD within the context of a range of psychosocial measures such as mood and everyday functioning. Adults with DCD were compared to a group of adults with Chronic Fatigue Syndrome (CFS) and a typically developing/ non-fatigued group. Method: Fifty-three adults with DCD, 84 with CFS and 52 typically developing/ non-CFS adults completed a range of established psychometric measures via an online data collection tool. Results: Findings demonstrated clear differences between the DCD and typically developing/ non-fatigued group for all measures administered, including fatigue ( p < 0.001). When compared to the CFS group, adults with DCD showed significantly lower levels of cognitive difficulties ( p < 0.05), fatigue ( p < 0.001), somatic symptoms ( p < 0.001), and total symptoms ( p < 0.001). However, no significant differences were found between the DCD and CFS groups in terms of anxiety, depression, cognitive failures, negative and positive affect, and self-esteem. Conclusions: Of particular importance in the current study was the capture of data that corroborated anecdotal evidence of heightened levels of fatigue in adults with DCD along with elevated symptomatology for depression, anxiety, and low self-esteem and difficulties with respect to cognitive functioning and restorative sleep.